Emerging viruses in the genus Comovirus - Petrzik, Karel; Koloniuk, Igor (Virus genes, 2010)
The intraspecies variability of capsid proteins of five viruses of the genus Comovirus was established. Inclusion of both capsid proteins to the sequence analysis reduces some uncertainties about species/strains demarcation criteria in the Comovirus genus. New approach is proposed for discrimination of Turnip ringspot virus as a separate species.
Keywords: Sequence Analysis, DNA; RNA, Viral; RNA virová; Comovirus; Capsid Proteins; Molecular Sequence Data; molekulární sekvence - údaje; sekvenční analýza DNA; Polymorphism, Genetic; virové plášťové proteiny; polymorfismus genetický